2020
DOI: 10.3390/su13010127
|View full text |Cite
|
Sign up to set email alerts
|

How Blue Carbon Ecosystems Are Perceived by Local Communities in the Coral Triangle: Comparative and Empirical Examinations in the Philippines and Indonesia

Abstract: Blue carbon ecosystem (BCE) initiatives in the Coral Triangle Region (CTR) are increasing due to their amplified recognition in mitigating global climate change. Although transdisciplinary approaches in the “blue carbon” discourse and collaborative actions are gaining momentum in the international and national arenas, more work is still needed at the local level. The study pursues how BCE initiatives permeate through the local communities in the Philippines and Indonesia, as part of CTR. Using perception surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…Furthermore, discussion on the ecosystem services in the boundary of coastal settings need to take place, such as the potential of blue carbon ecosystems services in mangroves and seagrass as marine resources in the utilization for carbon sequestration and tourism activities. Blue carbon ecosystem services of carbon sequestration in the mangrove and seagrass ecosystem in Karimunjawa was reported to be moderately aware by the locals, and in general the blue carbon functions are unrecognized compared with the services as coastal protection (Quevedo et al 2021a ). In future research, information of emissions from tourism sector and carbon sequestration function of blue carbon ecosystem can be shared with local residents as scientific evidence to support them to evaluate the status of coastal environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, discussion on the ecosystem services in the boundary of coastal settings need to take place, such as the potential of blue carbon ecosystems services in mangroves and seagrass as marine resources in the utilization for carbon sequestration and tourism activities. Blue carbon ecosystem services of carbon sequestration in the mangrove and seagrass ecosystem in Karimunjawa was reported to be moderately aware by the locals, and in general the blue carbon functions are unrecognized compared with the services as coastal protection (Quevedo et al 2021a ). In future research, information of emissions from tourism sector and carbon sequestration function of blue carbon ecosystem can be shared with local residents as scientific evidence to support them to evaluate the status of coastal environment.…”
Section: Discussionmentioning
confidence: 99%
“…Seven activity types were listed in the questionnaire, and a comments section was provided for listing respondents’ additional management activities (if any), which may not have been included in the questionnaire. The seven activity types adopted by Quevedo et al ( 2021a ) were (1) organization strengthening and capacity development; (2) coastal and fisheries law enforcement; (3) fisheries management; (4) enterprise, livelihood, and tourism development; (5) information and education campaigns; (6) coastal zoning; and (7) habitat management and marine sanctuaries. Respondents were asked to rank these seven activities from the most prioritized (score 1) to the least prioritized (score 7).…”
Section: Materials and Methodologymentioning
confidence: 99%
“…The distribution of the questionnaire was targeted to the practitioner of MSMEs sector in West Java province under training from the association of Indonesian micro and small entrepreneurs (HIPMIKINDO) with total of 250 entrepreneurs. In this study we calculated the sample size using Cochran's formula of: n = n 0 /(1+n 0 /N) (Quevedo, Uchiyama, Lukman, & Kohsaka, 2021). We set the confidence level to 95% and margin of error 5%.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, these services have been neglected through inadequate management, misled governance and gaps in social and scientific knowledge along with lack of local knowledge. A study reported by Quevedo et al (2021) documented that coastal ecosystem services are more likely to be acknowledged by a society which benefits directly from them; in other words, clearer pathways between ecosystem services and societies are key for populations to truly value an ecosystem as a whole. This explains partly why Pacific Island nations have been at the forefront of advancing ocean issues in climate policy.…”
Section: Coastal Carbonmentioning
confidence: 99%